Dynamic of changes in health of 10-11 years old gymnasium boys under influence of comprehensive education's load - E.M. Proskurov (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: determination of somatic health, physical condition, physical and mental workability changes of pupils under influence of comprehensive education loads at the end of first academic semester. Material: in the research 140 pupils of 10-11 years old age, related to main health group, participated. Results: we found that the reason of children' health's worsening appears at the account of increasing of intellectual pressure. This pressure can not be overcome by means of physical education, oriented on recreation and perfection of pupils' organisms. Absence of gradual relaxation of mental loads (periods of recreation and test after different intellectual tensions) results in sharpening of overtiredness at the end of first academic semester. This overtiredness negatively influences on pupils' general health. Conclusions: responses of children's organisms to irritators of comprehensive education's pressure are accompanied by worsening of a number of functional indicators, which have no age distinctions.